HASTO WARDOYO’S POPULISM - Mahmuddin Sirait (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2023)
This paper will discuss how Hasto Wardoyo exercised government power during his first leadership from 2011-2016. Using populism as an analytical tool, this paper argues that Hasto Wardoyo used two ways in exercising government power. Firstly, using populist programs. Secondly, doing direct interaction with people.